2020
DOI: 10.1108/jocm-01-2020-0029
|View full text |Cite
|
Sign up to set email alerts
|

Leadership behaviours that foster organisational identification during change

Abstract: PurposeTo better understand how leadership behaviours are operationalised to foster organisational identification during change, to maximise the success of change initiatives.Design/methodology/approachUtilising the Delphi Technique, 15 Australian senior leaders and leadership subject matter experts were canvassed regarding their opinions on the role of leadership in nurturing organisational identification during change. Their perspectives on a preliminary leadership competency framework developed in an earlie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 47 publications
0
11
0
2
Order By: Relevance
“…The fundamental purpose of change-oriented behaviour is to identify and implement desired changes in the leader's team or work unit's duties, outputs, or work procedures (Oygarden, 2020). The specific change-oriented behaviours include promoting change, fostering innovation, taking calculated risks and encouraging change (Aitken, 2020). The component behaviours are comparable to those of transformational leadership (Bass, 1985), charismatic leadership (Conger & Kanungo, 1987;House, 1977), and change management (Kotter, 1996).…”
Section: E Change-oriented Behaviourmentioning
confidence: 99%
“…The fundamental purpose of change-oriented behaviour is to identify and implement desired changes in the leader's team or work unit's duties, outputs, or work procedures (Oygarden, 2020). The specific change-oriented behaviours include promoting change, fostering innovation, taking calculated risks and encouraging change (Aitken, 2020). The component behaviours are comparable to those of transformational leadership (Bass, 1985), charismatic leadership (Conger & Kanungo, 1987;House, 1977), and change management (Kotter, 1996).…”
Section: E Change-oriented Behaviourmentioning
confidence: 99%
“…There is a considerable amount of literature and research that identifies various factors that can influence employee change readiness, including [1] communication (Endrejat et al, 2021;Neill, Men, & Yue, 2019;Schulz-Knappe, Koch, & Beckert, 2019), [2] leadership (Gelaidan et al, 2018;Indriastuti & Fachrunnisa, 2021;Islam, Furuoka, & Idris, 2021b, 2021a organizational culture (Olafsen, Nilsen, Smedsrud, & Kamaric, 2021;Samal, Patra, & Chatterjee, 2021;Trisnanto & Soetjipto, 2022;Wong, 2021), [4] organizational identification (Aitken & von Treuer, 2021;Hameed et al, 2019;Neill et al, 2019), and [5] change beliefs (Commer, Sci, Kashif Imran, Muhammad, & Iqbal, 2021;Hameed et al, 2019;Islam et al, 2021a;Mei Kin, Abdul Kareem, Nordin, & Wai Bing, 2018;Rafferty & Minbashian, 2019). Recently, Yean, et al (2022) attempted to identify other factors that may affect change readiness by conducting a study to examine the impact of several factors that are summarized as managerial climate, and adaptability on change readiness.…”
Section: Thementioning
confidence: 99%
“…Furthermore, Neill et al (2019) also find that organizational identification positively influences the factors of employees' change readiness. Aitken & von Treuer (2021) argue that organizational identification held by members within an organization is considered a pivotal factor that should be considered when an organization is planning a change initiative. Yean et al (2022) identified five dimensions of managerial climate which are trust, supportiveness, openness, clarity of goals, and participative.…”
Section: Thementioning
confidence: 99%
“…Роль лидеров заключается в создании оптимальной готовности и усилении институционализации относительно крупномасштабных организационных изменений в направлении корпоративной устойчивости [19]. Учитывая тот факт, что лидерское поведение способствует организационной идентификации в период неопределенности, в дальнейшем целесообразным является смещение вектора деятельности руководителей в такие области компетенций, как управление организационными изменениями, управленческая деятельность в коллективе, развитие коммуникативных навыков [20,21]. Кроме того следует отметить, что особое внимание руководителя должно быть направлено на выявление и последующую мотивацию агентов изменений, которые выступают катализаторами трансформации организации за счет поддержки, развития и контроля внедрения инноваций, принимают участие в создании команд, обеспечивают межгрупповое взаимодействие [22].…”
Section: рисунок 3 -системная готовность сотрудников к инновациямunclassified